Menopausal hormone therapy and central nervous system tumors: Danish nested case-control study. - Nelsan Pourhadi; Amani Meaidi; Søren Friis; Christian Torp-Pedersen; Lina S Mørch (PLoS Medicine, 2023)
Background Use of estrogen-containing menopausal hormone therapy has been shown to influence the risk of central nervous system (CNS) tumors. However, it is unknown how the progestin-component affects the risk and whether continuous versus cyclic treatment regimens influence the risk differently. Methods and findings Nested case-control studies within a nationwide cohort of Danish women followed for 19 years from 2000 to 2018. The cohort comprised 789,901 women aged 50 to 60 years during follow-up, without prior CNS tumor diagnosis, cancer, or contraindication for treatment with menopausal hormone therapy. Information on cumulative exposure to female hormonal drugs was based on filled prescriptions. Statistical analysis included educational level, use of antihistamines, and use of anti-asthma drugs as covariates. During follow-up, 1,595 women were diagnosed with meningioma and 1,167 with glioma. The median (first-third quartile) follow-up time of individuals in the full cohort was 10.8 years (5.0 years to 17.5 years). Compared to never-use, exposure to estrogen-progestin or progestin-only were both associated with increased risk of meningioma, hazard ratio (HR) 1.21; (95% confidence interval (CI) [1.06, 1.37] p = 0.005) and HR 1.28; (95% CI [1.05, 1.54] p = 0.012), respectively. Corresponding HRs for glioma were HR 1.00; (95% CI [0.86, 1.16] p = 0.982) and HR 1.20; (95% CI [0.95, 1.51] p = 0.117). Continuous estrogen-progestin exhibited higher HR of meningioma 1.34; (95% CI [1.08, 1.66] p = 0.008) than cyclic treatment 1.13; (95% CI [0.94, 1.34] p = 0.185). Previous use of estrogen-progestin 5 to 10 years prior to diagnosis yielded the strongest association with meningioma, HR 1.26; (95% CI [1.01, 1.57] p = 0.044), whereas current/recent use of progestin-only yielded the highest HRs for both meningioma 1.64; (95% CI [0.90, 2.98] p = 0.104) and glioma 1.83; (95% CI [0.98, 3.41] p = 0.057). Being an observational study, residual confounding could occur. Conclusions Use of continuous, but not cyclic estrogen-progestin was associated with increased meningioma risk. There was no evidence of increased glioma risk with estrogen-progestin use. Use of progestin-only was associated with increased risk of meningioma and potentially glioma. Further studies are warranted to evaluate our findings and investigate the influence of long-term progestin-only regimens on CNS tumor risk.